ANALISIS PREFERENSI PLATFROM E-COMMERCE DAN PERILAKU BELANJA KONSUMEN DIGITAL LINTAS GENERASI DI PASAR INDONESIA - Zerah Elisa Derek; Yoan Purnamsari Makapuase Bahalau; Marthin Thomas Mumbunan (ITB AAS Indonesia Surakarta, 2026)
This study examines the impact of generational characteristics on e-commerce platform preferences and purchasing decisions in Indonesia. By analyzing Gen Z, Millennials, and Baby Boomers, the research highlights a significant shift in digital behavior. Gen Z predominantly favors visual-based platforms like TikTok Shop, driven by social trends and